Relationship In Intrinsic Learning Motivation with Cognitive Learning Competency of Sains Students In Class VII Junior High School 16 Padang - Septia Utari; Rahmadhani Fitri; Sa'diatul Fuadiyah; Relsas Yogica (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Many factors influence cognitive competency in learning, one of which is student motivation. Motivation is an impulse that is contained in a person to try to make behavioral changes that are better in meeting their needs. Learning motivation is basically divided into two, namely intrinsic motivation and extrinsic motivation. Intrinsic motivation is motivation that arises from within the individual himself without any coercion or encouragement from others, but on the basis of his own will. While extrinsic motivation is an encouragement from outside a person. This study aims to determine the relationship between intrinsic learning motivation and IPA cognitive learning competencies of class VII students of SMP 16 Padang. This study is a descriptive study that seeks the relationship between two variables. Data analysis using Pearson Product Moment correlation formula to see how the relationship between intrinsic learning motivation and science learning cognitive competencies. Correlation analysis to see how much the relationship between motivation and learning competence and t-test analysis contributed to see the significance of a relationship. Data collection techniques used in this study were research instruments in the form of questionnaires on students' metacognitive abilities. The biology learning competency value of VII grade science students of SMP 1 Padang is taken from students' daily test scores in the second semester of the 2018/2019 academic year. The results showed that there was no positive and significant relationship between learning motivation and students' IPA cognitive learning outcomes in class VII of 16 Padang Junior High School with a tcount of 0.78, and ttable of 1,697The correlation of learning motivation with learning competencies is in the very low category with a value of r = 0.14.